Analysis of The Achievement of The Minimum Service Standard See From the Quality of Service and Patient Satisfaction In The Installation Of Pharmaceutical Pharmaceuticals In RSI Malang "UNISMA" - Musyrifah; Imam Suprapto, Sentot; Sari, Nia (Journal for Research in Public Health, 2019)
Facing the era of intense competition that needs to be trained by hospitals is patient satisfaction, patient satisfaction is closely related to quality service quality and service quality is evaluated by achieving minimum service standards that are in accordance with standards. The existence of preliminary data from the RSI about pharmacy service satisfaction figures in terms of facilities 95.2%, waiting time 77.4%, friendliness 95.2%, accuracy 91.9%, where this data still needs more in-depth research to obtain satisfaction figures valid. The purpose of this study was to determine the effect of service quality on patient satisfaction and the achievement of Minimum Service Standards for outpatient pharmacy installation in Malang Hospital "Unisma". This type of research is quantitative with observational analytic using cross sectional. The population in this study were all patients who visited who had received medication services, taking samples by simple random sampling of 136 samples, using questionnaires. Analyze data with path analysis. The results showed that the path coefficient of Service Quality to satisfaction of 0.425 showed a positive effect. The path coefficient of Service Quality towards achievement of MSS of 0.413 shows a positive influence, the path coefficient of Patient Satisfaction with achievement of MSS of 0.166 shows a positive influence. To improve the quality of service, it will be followed by achieving good standards, so patient satisfaction will also increase. From the results of this study it can be concluded that the better the Quality of Service, the better Patient Satisfaction. The better the Quality of Service, the better the Achievement of Minimum Service Standards and the better the Patient Satisfaction, the better the Quality of Service Standards.